First report of Fusarium oxysporum Species Complex causing root and rhizome rot of Canna edulis in Colombia - Ortega, Maria Camila (Plant disease, 2023)
Achira, Canna edulis Ker, a plant native to South America, is the source of a starch used for food and industrial purposes. Since 2016, Colombian growers of the main cropping regions, Cundinamarca (CU), Nariño (NA), and Huila (HU) are experiencing yield losses due to rhizome rots. Surveys of the affected areas evidenced wilting and collapsed plants, with oxidized rhizomes and affected root masses. Disease incidence per field was around 10%, but diseased plants were found in all 44 visited farms. To study this problem, wilting plants were collected, and symptomatic tissues, pseudo-stems, roots, and rhizomes, were cut and disinfested in 1.5% hypochlorite, rinsed in sterile water, and plated onto PDA amended with 0.01% tetracycline. A total of 121 isolates were recovered; of these, 77 Fusarium-like isolates stood out, given their recovery frequency (64.7%) and cross-region distribution. To morphologically study the isolates, carnation leaf agar cultures of NA01, NA16, NA48, CU08-1 and HU02, were made. Isolates had hyaline, mostly aseptated microconidia, oval in shape, developing in false heads with short monophialides. Macroconidia were hyaline and falcate, straight to slightly curved, 2 to 4 septate, with apical cells curved and basal cells foot shaped. For NA01 the average size and width of the microconidia was 4.3 x 3.2 μm (n=80), while macroconidia averaged 18.9 × 5.7 μm (n =80); NA16 was slightly bigger (6.5 x 3 and 22.9 x 5.5 um respectively). This morphology resembles Fusarium oxysporum (Fox) (Leslie et al. 2006). Identity confirmation was obtained by Sanger sequencing of the rRNA internal transcribed spacer (ITS) and the translation elongation factor 1α (TEF1α) loci using protocols of White et al. 1994, and O'Donnell et al. 1998. Blast comparisons against NCBI databases, showed a very high identity (>99.5%) to MN528565.1 (ITS), and KU985430.1 (TEF 1α), both, F. oxysporum sequences. The identity of NA01 and CU08 was further confirmed by sequencing the DNA-directed RNA polymerase II (RPB1) locus (O'Donnell et al. 2015), observing more than 99% identity to CP052885.1 (RPB1) a F. oxysporum strain. BLAST check against the Fusarium MLSD database confirmed the identity. The obtained sequences were deposited in NCBI as MN963788, MN963793, MN963801, MN963782, MN963786 (ITS); OK143597, OK141601, OK143596 MW594202, OK169575 (TEF1α); and ON297670 and MZ670431 RPB1). To confirm causality, pathogenicity assays were conducted using NA01, NA48 and CU08. To this end, 25, 35 day-olds sprouted rhizomes, from each of the "purple", "green" and "white" varieties, were inoculated by drench with 30 ml of conidium suspension (1x106 conidia/ml) (Schmale 2003). Control rhizomes (25 per variety) were treated with sterile distilled water. Greenhouse conditions were 25 °C, 40% RH, and photoperiod 12h. Disease symptoms were detected 10 days after inoculation and evolved to resemble those from the field. While symptom and severity of infection varied with the isolate and host combination used, pathogen re-isolation and identification was successful fulfilling Koch´s postulates. Control plants remained healthy. The data shows that F. oxysporum species complex is the causal agent of this achira root and rhizome rot. To our knowledge, this is the first report of this problem in Colombia and clarifies local reports of Fusarium sp. causing disease in this crop (Caicedo et al. 2003). The disease affects the food security of local communities and strategies for control are being developed